(untitled) (Pravaha, 2021)
The purpose of this research is to assess an association between decent work and employee motivation in the context of industrial estates of Nepal. In order to ascertain the association between them, this study takes into account six different types of employee motivation and seven criteria for decent work. The study employs a five-point Likert scale questionnaire using a survey research technique to examine the association between decent work and employee motivation. 450 people from the three industrial estates who work for diverse organizations make up the sample (including 30 companies and 15 workers in each). They were given a standardized questionnaire, and only 379 (84.22%) valid responses were received, which were then included in the study. The results embraced the idea that decent work has a significant association with employee motivation at the workplace. In fact, employee motivation generally appears to be enhanced by all dimensions of decent work, with favorable associations between identified and intrinsic work motivation and negatively associated with amotivation. In conclusion, decent work allows workers to balance work and personal life, develop personally and professionally, etc. It improves both work and life quality and also plays a significant role in organizational performance by increasing employee motivation. Therefore, in order to increase employee motivation and ultimately increase organizational performance and the long-term sustainability of today’s organizations, they must create effective working environments and promote the concept of decent work in their workplaces.